A Screen for Genetic Loci Required for Body-Wall Muscle Development during Embryogenesis in Caenorhabditis Elegans - Ahnn, J. (1994)
We have used available chromosomal deficiencies to screen for genetic loci whose zygotic expression is required for formation of body-wall muscle cells during embryogenesis in Caenorhabditis elegans. To test for muscle cell differentiation we have assayed for both contractile function and the expression of muscle-specific structural proteins. Monoclonal antibodies directed against two myosin heavy chain isoforms, the products of the unc-54 and myo-3 genes, were used to detect body-wall muscle differentiation. We have screened 77 deficiencies, covering approximately 72% of the genome. Deficiency homozygotes in most cases stain with antibodies to the body-wall muscle myosins and in many cases muscle contractile function is observed. We have identified two regions showing distinct defects in myosin heavy chain gene expression. Embryos homozygous for deficiencies removing the left tip of chromosome V fail to accumulate the myo-3 and unc-54 products, but express antigens characteristic of hypodermal, pharyngeal and neural development. Embryos lacking a large region on chromosome III accumulate the unc-54 product but not the myo-3 product. We conclude that there exist only a small number of loci whose zygotic expression is uniquely required for adoption of a muscle cell fate.